(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
We, the authors, are emotionally and physically disturbed. The disturbance we are experiencing is most particularly sourced in our nation’s collective resistance to speaking out against our various and ongoing military actions worldwide. This specific emotional and physical disturbance has given rise to a more general educational concern: when we do not meet our democratic educational obligation to nurture the embodied emotional seed that is essential to critical reflection, peaceful civic activism can and will wither on the vine.